Not Quite What You Expected: The Curious Case of Brexit Scrutiny in the Czech Parliament. Issue 1 (4th August 2019) - Kaniok, Petr; Brusenbauch Meislova, Monika
Abstract: The aim of the article is to explore how the Czech bicameral parliament has reacted to the process of the United Kingdom's (UK's) withdrawal from the European Union (EU). Drawing upon insights from the theoretical expectations of parliamentary power, the inquiry researches the ways that Czech legislatures have developed in terms of engaging with and influencing the Brexit process. In this regard, the Czech case is exceptionally interesting and worth exploring, since the EU agenda has become a highly politicised issue within the Czech context. The significance of this inquiry has been further highlighted by the high level of party-based Euroscepticism typical of Czech politics as well as the frequent changes that the Czech party system has been undergoing in recent years. Throughout the in-depth analysis of parliamentary scrutiny activities—conceptualised as comprising four aspects: (i) the institutional adjustment; (ii) articulation of priorities; (iii) interactions with the government and (iv) parliamentary party politics—the article considers how these activities compare between both chambers of the Czech Parliament.